2012
DOI: 10.1097/aap.0b013e318236bc30
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Blind Randomized Clinical Trial of Time Until Sensory Change Using 1.5% Mepivacaine With Epinephrine, 0.5% Bupivacaine, or an Equal Mixture of Both for Infraclavicular Block

Abstract: Mixing 1.5% mepivacaine (with epinephrine) with 0.5% bupivacaine speeds up PNB sensory (motor) onset compared with 0.5% bupivacaine alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Another study reported a median (range) time to onset of 6 (3–12) minutes for 40 mL of 0.5% bupivacaine. 18 However, these studies did not compare different volumes; thus, the evaluation of time to onset may have been less strict than in the present study. Indeed, the evaluation of sensory block in the latter study depended on the patients reporting a “different” (as opposed to the “same”) sensation during the touch test.…”
Section: Discussionmentioning
confidence: 69%
“…Another study reported a median (range) time to onset of 6 (3–12) minutes for 40 mL of 0.5% bupivacaine. 18 However, these studies did not compare different volumes; thus, the evaluation of time to onset may have been less strict than in the present study. Indeed, the evaluation of sensory block in the latter study depended on the patients reporting a “different” (as opposed to the “same”) sensation during the touch test.…”
Section: Discussionmentioning
confidence: 69%
“…Laur et al found that the number of patients feeling surgical incision (7 out of 31), block failure rate (6 out of 31) and GA conversion rate (4 out of 31) were significantly higher with bupivacaine even after 64 (50-84) minutes of the needle out to incision time. 3 In the present-day practice of US-guided precise injection techniques, where the MELAV for the US-guided supraclavicular BPB is below 20 mL, worries about the additive effect on toxicity caused by mixing of LA are also of no clinical relevance. 8 9 The limitation of our study is that we did not wait beyond 40 min to note the time for CCB in the bupivacaine group.…”
Section: Original Researchmentioning
confidence: 99%
“…3 5 However, our finding of the duration of analgesia following LA mixture as significantly more than lidocaine and less than bupivacaine is well reported by many authors. [3][4][5] We represented 20 mL as low volume for USG-SCBPB. This is based on our experience that 5-6 mL more than the MELAV-99 will provide satisfactory duration of surgical anesthesia and analgesia for the most common bony surgical procedures of the elbow and forearm.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Wirkdauer der Mischung war zwar länger als bei Anwendung von Mepivacain allein, aber auch deutlich kürzer als bei alleiniger Nutzung von Bupivacain. Folgestudien für weitere periphere RA-Verfahren zeigten ein ähnliches Muster keiner oder nur klinisch irrelevant beschleunigter Anschlagzeit und gleichzeitig verkürzter Wirkdauer von LA-Mischungen gegenüber langwirksamen Substanzen[25,26,27].PR A XISEMPFEHLUNGGerade bei Blockaden, bei denen eine besonders lange Wirkdauer gewünscht ist, sollte man keine Mischung von langwirksamen LA und LA mit kurzer Wirkdauer vornehmen. Vielmehr sollten lediglich Bupivacain oder Ropivacain in adäquater Dosis (und kombiniert mit einem Adjuvans wie intravenösem Dexamethason[28]) als Monosubstanzen verwendet werden.…”
unclassified